Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s13204-015-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear oscillation of nanoelectro-mechanical resonators using energy balance method: considering the size effect and the van der Waals force

Abstract: The energy balance method is utilized to analyze the oscillation of a nonlinear nanoelectro-mechanical system resonator. The resonator comprises an electrode, which is embedded between two substrates. Two types of clamped-clamped and cantilever nano-resonators are studied. The effects of the van der Waals attractions, Casimir force, the small size, the fringing field, the mid-plane stretching, and the axial load are taken into account. The governing partial differential equation of the resonator is reduced usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The nonlinear vibration of an electrostatically-actuated nanobeam with van der Waals, Casimir and fringing effects can be modelled as (Ghalambaz et al, 2016):…”
Section: Electrostatically-actuated Nanobeam With Weak Interacting Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear vibration of an electrostatically-actuated nanobeam with van der Waals, Casimir and fringing effects can be modelled as (Ghalambaz et al, 2016):…”
Section: Electrostatically-actuated Nanobeam With Weak Interacting Forcesmentioning
confidence: 99%
“…The error analysis of Figure 2b showed that the nanobeam undergoes a linear to weakly nonlinear response for 0 < < 0.35, while a strong nonlinear response was predicted when > 0.475. Equations ( 8) was studied by Ghalambaz et al (2016) using the energy balance method (EBM) while Ismail et al (2019) used the global residue harmonic balance method (GRHBM). The EBM solution was simulated for = 0.01 while the GRHBM was applied for ≤ 0.50.…”
Section: Electrostatically-actuated Nanobeam With Weak Interacting Forcesmentioning
confidence: 99%
“…Moreover, the BVP (1), (2) has been analyzed by meshless method through radial basis functions, though they are often used for high-dimensional problems [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The interested readers are also referred to [36][37][38][39] for other useful techniques, which can be applied for the same problems.…”
Section: Preliminaries and Mathematical Formulationmentioning
confidence: 99%
“…biosensors, micro-resonators, atomic force microscopes (AFMs) and actuators [1][2][3][4]. MEMS/NEMS may be actuated using several sources of energy such as electrostatic [5], electromagnetic [6], piezoelectric [7] and may be made of metals or polymer, silicon-based structures or functionally graded materials (FGM) [8][9][10][11][12][13]. Electrostatic actuation has demonstrated good energy density and efficiency.…”
Section: Introductionmentioning
confidence: 99%